APPLICATION OF UNDERWATER PHOTO TRANSECT METHOD TO UNDERSTAND CORAL REEFS COVER IN POMBO ISLAND, MALUKU - Arif Seno Adji; Terry Indrabudi; Robert Alik (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Methods to understand coral reefs health are increasingly diverse. One of the promising method is georeferenced photo transect. In this method, a diver took benthic community photos using a camera installed or connected with a Global Positioning System (GPS) receiver, so that each photo taken has a geographic coordinate on it. This spatial information is very useful for monitoring coral reefs health. The purpose of this research is to understand coral reefs cover in Pombo Island, Maluku by using georeferenced photo transect method. Field data collection was done in April 2015 with 14 transect lines. Overall of 14 transect lines, 3 transects are in Good category, other 3 transects are in Pretty Good category, and the rest of 8 transects are in Not Good category. Coral species commonly found around transect lines are Porites lutea, Porites lobata, Acropora valenciennesi, Acropora hyacinthus, Turbinaria mesenterina, Stylophora pistillata, Mycedium elephantotus, Acropora latistella